Nanosecond and femtosecond fiber lasers using tungsten trioxide, poly (3,4-ethylenedioxythiophene) polystyrene sulfonate and turmeric saturable absorbers / Ahmed Shakir Abdullah Abdullah - Ahmed Shakir , Abdullah Abdullah (2021)
Nanosecond and femtosecond fiber lasers have been intensively investigated in recent years for applications in material processing, imaging, and medical treatment because of the low thermal effect and high pulse energy. Passive techniques based on saturable absorber (SA) offer advantages over their active counterparts due to their unique electronic and optical properties as well as no need of external electrical modulation. This work was successfully explored three new materials: tungsten tri-oxide, poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT: PSS), and turmeric [1, 7-bis (4-hydroxy-3-methoxyphenyl)-1, 6 heptadiene-3, 5-dione] as the passive SA. These SAs were successfully fabricated, characterized, and utilized in generating Q-switched and mode-locked pulses in various fiber laser cavities. The highest modulation depth of 50 % was obtained by the organic SA fabricated by embedding PEDOT: PSS into PVA film. Various Q-switched fiber lasers were also demonstrated based on the newly developed SAs. For instance, Q-switched YDFL operating at 1063.78 nm was demonstrated using WO3 PVA thin film as SA. It generated Q-switched pulses with the maximum repetition rate of 39.79 kHz, minimum pulse width of 2.37 μs and maximum pulse energy of 625 nJ. The lowest pulse width of 580 ns was obtained with the organic SA based PEDOT: PSS embedded into PVA film. Various mode-locked fiber lasers operating in picosecond and femtosecond regimes were also realized using the newly developed SAs. At optimized design with a cavity length of 22.5 m, a soliton femtosecond pulse with 460 fs pulse width and peak power of 4.27 kW, was successfully achieved. This work has also successfully drawn attention to the potentials that organic materials have in fiber laser selakan-mod. Mereka serasi dengan bio, mesra alam, ringan dan fleksibel secara mekanikal.